TINGKAT KEPUASAN WISATAWAN MANCANEGARA TERHADAP KUALITAS PELAYANAN JASA PEGUYUBAN TRANSPORT BALE AGUNG UBUD - IPMM. Manuaba; I Ketut Suwena; NGAS. Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The increasing number of foreign tourists visiting Ubud, makes local people take advantage of these opportunities for transportation services business. Many people own a car, selling roadside transportation services in Ubud. So came the idea of the local community to form a group called Peguyuban Transport Bale Agung Ubud abbreviated ptbau. Therefore, this study is important to be carried out, in order to help PTBAU to measure the level of satisfaction of foreign tourists who use ptbau services. This study was conducted in Ubud Village using 105 respondents determined based on the concept of J.Supranto (2006) indicator multiplied by 5, samples in this study were selected using purposive sampling method. Data collected through questionnaires distributed when tourists use PTBAU services, then analyzed using Importance Performance Analysis and Customer Satisfaction Index. The results of this study were1) Characteristics of tourists who dominate from Germany, female gender, middle-aged, have the last education of high school equivalent, work as a private employee, married, first visit to Bali and use the services of PTBAU, visiting with friends, with a stay of 4-7 days, modes of transportation used for tours, accommodation used by hotels, and large daily expenses of Rp. <1,000,000. 2) The level of satisfaction of foreign tourists to the quality of services Peguyuban Transport Bale Agung Ubud is in the category of satisfied and priority that takes precedence in the improvement is the appearance and neatness of drivers, the price offered, the response of tourists to tourist questions, and security when tourists tour.